2023
DOI: 10.3390/ijms241411356
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as a Tool for Early Diagnosis of Endometrial Cancer—Implications for the Fertility-Sparing Process: Clinical, Biological, and Legal Aspects

Abstract: This review article explores the possibility of developing an integrated approach to the management of the different needs of endometrial cancer (EC) patients seeking to become pregnant. Life preservation of the woman, health preservation of the baby, a precocious and—as much as possible—minimally invasive characterization of the health and fertility parameters of the patient, together with the concerns regarding the obstetric, neonatal, and adult health risks of the children conceived via assisted reproductiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 165 publications
0
17
0
Order By: Relevance
“…Accumulating evidence suggests that employing conservative approaches and close monitoring until delivery does not compromise the survival outcomes of endometrial cancer patients. For patients without male partners or those unwilling to cryopreserve embryos, oocyte preservation can be achieved through vitrification and slow cooling techniques 31,32 . Notably, vitrification techniques mitigate the risk of multiple pregnancies and ovarian hyperstimulation syndrome 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that employing conservative approaches and close monitoring until delivery does not compromise the survival outcomes of endometrial cancer patients. For patients without male partners or those unwilling to cryopreserve embryos, oocyte preservation can be achieved through vitrification and slow cooling techniques 31,32 . Notably, vitrification techniques mitigate the risk of multiple pregnancies and ovarian hyperstimulation syndrome 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…For patients without male partners or those unwilling to cryopreserve embryos, oocyte preservation can be achieved through vitrification and slow cooling techniques. 31 , 32 Notably, vitrification techniques mitigate the risk of multiple pregnancies and ovarian hyperstimulation syndrome. 31 , 32 For babies conceived by assisted reproductive technologies, including oocyte cryopreservation, the long‐term health implications warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertility preservation (FP) emerged as a treatment aiming to preserve future reproductive capacity of individuals facing therapies that could potentially affect their gonads [102] or if needed to perform a fertility sparing surgery treatments in case of diagnosis of malignancies and especially in reproductive age [103][104][105][106][107]. The majority being patients diagnosed with cancer, cryopreservation of oocytes or embryos by vitrification [108] is the most common way to preserve fertility and for future needed especially at the parentinghood time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hundreds of ncRNAs are potentially deregulated in EC and ncRNAs can be detected in the blood circulation; therefore, circulating ncRNAs can be fast, accurate, and minimally invasive diagnostic tools. 44 , 47 Circulating micro RNAs of EC patients as diagnostic, prognostic and therapeutic markers could be potentially applicable for personalized medicine in the future. 44 …”
Section: Discussionmentioning
confidence: 99%